Flottement Du Taux De Change Et Incomplétude De La Transmission De La Politique Monétaire Au Taux Débiteur - Hassan Hachimi Alaoui (European Scientific Journal, ESJ, 2017)
This paper presents a partial equilibrium model of the credit market where the interference between nominal exchange rate, banks' balance sheet and credit channels of monetary policy transmission give rise to an incomplete pass through to the lending rate. The model shows that the overlapping of these three channels under floating exchange rate regime and external debt with endogenous risk premium is the cause of a conflictual effect of monetary shocks on banks behavior. This is in line with research highlighting externalities of floating exchange rate regime.